Legal Protection Policy for Domestic Workers Through Legal Certainty - Ikhsan Sahriyan; Muhammad Fazli Pratama; Rahman Al-Fauzi Siregar; Ahmad Yasin Dongoran; Nurhafizah Husna (ISNU Sumatera Utara, 2025)
This study examines the legal protection of domestic workers (PRT) in Indonesia through the aspect of legal certainty. The study results indicate that legal protection for domestic workers remains very weak, due to the absence of specific regulations that explicitly regulate their status, rights, and obligations. Existing regulations, such as the Manpower Law, do not directly accommodate the needs of domestic workers because the long-initiated Domestic Worker Protection Bill has not yet been passed. This condition creates an uncertain legal position for domestic workers and makes them vulnerable to various forms of rights violations, exploitation, and violence. International comparisons show that Indonesia still lags behind in building a fair and inclusive protection system for domestic workers. Therefore, strategic steps are needed to develop comprehensive regulations and provide legal certainty to effectively protect the basic rights of domestic workers. This research is expected to contribute to the development of more just and sustainable legal policies for domestic workers in Indonesia.